Systemic feedback modelling for sustainable water resources management and agricultural development: An application of participatory modelling approach in the Volta River Basin. (February 2017) - Kotir, Julius H.; Brown, Greg; Marshall, Nadine; Johnstone, Ron
Abstract: Although our understanding of water resource problems has grown in recent years, our ability to improve decision-making is still limited. Participatory modelling and stakeholder engagement is seen as an important tool that can facilitate strategic decision-making in environmental/natural resource management systems. This paper presents the participatory and methodological processes involved in the development of an integrated qualitative, conceptual model using causal loops diagrams to assist integrated water resources management and sustainable agricultural development in the Volta River Basin, West Africa. The developed integrated conceptual model provides a holistic understanding of the key biophysical and socio-economic factors and processes, and the role the systemic feedbacks play in determining the basin's behaviour. An ex-post analysis of the process with stakeholders showed that the process contributed to the shared understanding of the basin's problems. Based on our experience we present some lessons for the design and application of a participatory modelling process. Graphical abstract: Highlights: Causal loop diagrams used as tools to develop an integrated conceptual model at the basin scale. Conceptual model integrates biophysical, socio-economic, and policy sub-sectors. Multi-disciplinary stakeholders involved in the development of the model. Identification of a number of key reinforcing and balancing feedback loops. Challenges and experience of conducting participatory modelling presented.